Rational design of low immunogenic anti CD25 recombinant immunotoxin for T cell malignancies by elimination of T cell epitopes in PE38 - Mazor, Ronit (Cell Immunol, 2017)
LMB-2, is a potent recombinant immunotoxin (RIT) that is composed of scFv antibody that targets CD25 (Tac) and a toxin fragment (PE38). It is used to treat T cell leukemias and lymphomas. To make LMB-2 less immunogenic, we introduced a large deletion in domain II and six point mutations in domain III that were previously shown to reduce T cell activation in other RITs. We found that unlike other RITs, deletion of domain II from LMB-2 severely compromised its activity. Rather than deletion, we identified T cell epitopes in domain II and used alanine substitutions to identify point mutations that diminished those epitopes. The novel RIT, LMB-142 contains a 38 kDa toxin and nine point mutations that diminished T cell response to the corresponding peptides by an average of 75%. LMB-142 has good cytotoxic activity and has lower nonspecific toxicity in mice. LMB-142 should be more efficient in cancer therapy because more treatment cycles can be given.